Wound healing activity of Cleome rutidosperma DC. roots - Mondal, Sumanta; Suresh, Padilam (International Current Pharmaceutical Journal, 2012)
The petroleum ether, chloroform, methanol and aqueous extracts of Cleome rutidosperma DC (Family: Capparidaceae) roots were evaluated for their wound healing activities in rats using excision and incision wound models respective-ly. The effects of test samples on the rate of wound healing were assessed by the rate of wound closure, period of epithelialisation and wound breaking strength. Nitrofurazone (0.2% w/w) in simple ointment I.P. was used as reference standard for the activity comparison. The results of the study revealed that the animals treated with methanol and aqueous extracts of C. rutidosperma showed faster rate of wound healing compared to other extracts under study. The chloroform extract of the selected plant also produced promising results but the effects are seen to be of lesser extent than the corresponding methanol and aqueous extracts. The petroleum ether extract did not produce significant results. The present work justifies the use of C. rutidosperma roots for wound healing activity as claimed in the folklore literature. DOI: http://dx.doi.org/10.3329/icpj.v1i6.10536 International Current Pharmaceutical Journal 2012, 1(6): 151-154